Upaya Meningkatkan Hasil Belajar Matematika Dengan Menggunakan Mode Kertas Quizizz Siswa Kelas IV SD Negeri 6 Cakranegara Tahun Pelajaran 2022/2023 - Prajaniti, Ni Nyoman Windra; Sahdi, Sahdi; Herawati, Sri; Intiana, Siti Rohana Hariana (Journal of Science Instruction and Technology, 2023)
This classroom action research aims to improve learning outcomes in learning Mathematics through the Quizizz paper mode method for fourth-grade students at SD Negeri 6 Cakranegara. This type of research is classroom action research (PTK) while the approach uses a descriptive quantitative approach. This research was conducted at SD Negeri 6 Cakranegara. The subjects of this study were fourth-grade students consisting of 31 students. the object of this research is the result of learning. The research was conducted in two cycles and was carried out collaboratively between researchers and tutors. Data collection techniques used are tests and observation sheets. The results of this study indicate that the application of the Quizizz paper mode in learning, especially as an evaluation tool, can improve the learning outcomes of fourth-grade students at SD Negeri 6 Cakranegara. This increase is shown by the quality of the learning process, liveliness, enthusiasm, and enthusiasm as well as test scores on student learning outcomes. the increase can be seen from the average score of students' test results from pre-action to cycle II. In the pre-action, the average student score was 63, increased in cycle I to 74, then experienced another increase in cycle 2 of 78. The percentage of completeness from cycle I and cycle II was 67.74% (21 students) respectively increasing in cycle II to 83.87% (26 students). Because it has reached the completeness criteria, namely 75% of students get scores more than or equal to KKM (75), this research is said to be successful.